2020
DOI: 10.1016/j.ejmech.2020.112471
|View full text |Cite
|
Sign up to set email alerts
|

Drug repurposing: Discovery of troxipide analogs as potent antitumor agents

Abstract: Drug repurposing plays a vital role in the discovery of undescribed bioactivities in clinical drugs. Based on drug repurposing strategy, we for the first time reported a novel series of troxipide analogs and then evaluated their antiproliferative activity against MCF-7, PC3, MGC-803, and PC9 cancer cell lines and WPMY-1, most of which showed obvious selectivity toward PC-3 over the other three cancer cell lines and WPMY-1. Compound 5q, especially, could effectively inhibit PC3 with an IC 50 value of 0.91 mM, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…This strategy cuts research costs and speeds up drug usage as the repurposed drugs have already been deemed safe in preclinical models and humans. As a result, drug repurposing has achieved great success, leading to the identification of candidate drugs for a pleura of diseases [208].…”
Section: Drug Repurposingmentioning
confidence: 99%
“…This strategy cuts research costs and speeds up drug usage as the repurposed drugs have already been deemed safe in preclinical models and humans. As a result, drug repurposing has achieved great success, leading to the identification of candidate drugs for a pleura of diseases [208].…”
Section: Drug Repurposingmentioning
confidence: 99%
“…Developing antitumor therapeutics have typically encountered several restrictions in terms of clinical impacts, especially for their side effects against healthy tissues. [258] Although numerous in vitro studies have indicated that MBGs combined with chemotherapy agents and ions could suppress tumor cells' activity with limited toxicity against normal cells, there are limited precise in vivo studies and almost nonexistent clinical research in this field. In light of this, a significant issue that should be carefully investigated in the future is the risk of toxicity in a broad context, including systemic, tissues, and organs affected by MBGs.…”
Section: Paving the Way For Clinical Translationmentioning
confidence: 99%
“…A troxipida apresenta atividade anti-inflamatória e é utilizada no tratamento de refluxo 5 . Através de modificações químicas, Lu et al (2020) demonstraram a eficácia dos análogos de troxipida no combate de células de câncer de próstata, assim como de outros cânceres. Os pesquisadores determinaram a concentração inibitória média (IC50) de 22 derivados análogos à troxipida onde 11 demonstraram atividade contra as células do câncer de próstata.…”
Section: Structure-activity Relationship Of Troxipide Analogs With In...unclassified